Technology dissemination of Beauveria bassiana bioinsecticide and Trichoderma biofungicide for controlling pests and diseases on shallots - Mohammad Yunus; Burhanuddin Haji Nasir; Nur Edy; Moh. Hibban Toana; Usman Made; Asgar Taiyeb (Universitas Muhammadiyah Magelang, 2022)
Pest and disease attacks are one of the obstacles in increasing shallot production in the Palu Valley, Central Sulawesi. Farmers still rely on the use of synthetic pesticides to control pests and diseases, which results in a high demand for insecticides and fungicides. This community service aims to disseminate pest control technology with the bioinsecticide Beauveria bassiana and disease control with the biofungicide Trichoderma, as well as train farmers to develop and apply it on their farms to solved the problems. The methods applied are training, technology application demonstration plots, coaching, and mentoring. The results of the activity showed that the participants were able to make and develop the bioinsecticide Beauveria bassiana and the biofungicide Trichoderma well. The application of bioinsecticides and biofungicides on demonstration plots reduced the intensity of onion caterpillar attacks and stem rot disease of shallots. With these results, farmers are expected to be able to develop and apply them in their farms.